Meaning in Language: A Contemporary Philosophical Review - Srisna J. Lahay; Sonya Ayu Kumala; Zweta Manggarani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to describe the position of meaning in language in the realm of philosophy; describes the thoughts and focus of language philosophy on meaning in language in the 20th century; and describes the impact of philosophy on research in contemporary linguistics. Literature study and text analysis methods were carried out to elaborate on the relationship between language and philosophy, the thoughts and focus of the philosophy of language, as well as the implications of the philosophy of language for contemporary linguistics research. There are four stages of activity in this research, namely (1) preparing the tools needed; (2) preparing a working bibliography; (3) arranging working time; and (4) reading and taking notes on research materials. The data collected is information and facts from various scientific works on the contemporary philosophy of language & linguistics. The data analysis phase was carried out when recording the information and facts and grouping them based on the problem unit under study and its contents. After that, data verification was carried out by testing the validity of the source of information and the content in the text. It was found that philosophy is closely related to language, which is the result of human cognition and has a function to convey the results of this cognition, and that contemporary philosophy argues that language is closely related to reality and has its own form, rules and uniqueness and states that meaning in language has forms, structure, and substance as well as empirical characteristics. This thinking influences the search for meaning in language and determines research trends on language, including research on the meaning of language in discourse, in names, and in natural speech. These studies consider aspects of form, substance, and also meaning in language. Research on meaning is needed to answer problems about language in this digital era. Keywords: meaning, language, philosophy of language, contemporary philosophy